2013
DOI: 10.1016/j.jmr.2012.11.028
|View full text |Cite
|
Sign up to set email alerts
|

W-band orientation selective DEER measurements on a Gd3+/nitroxide mixed-labeled protein dimer with a dual mode cavity

Abstract: Double electron-electron resonance (DEER) at W-band (95 GHz) was applied to measure the distance between a pair of nitroxide and Gd(3+) chelate spin labels, about 6 nm apart, in a homodimer of the protein ERp29. While high-field DEER measurements on systems with such mixed labels can be highly attractive in terms of sensitivity and the potential to access long distances, a major difficulty arises from the large frequency spacing (about 700 MHz) between the narrow, intense signal of the Gd(3+) central transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 34 publications
0
49
0
Order By: Relevance
“…3c. 40 In combining the NO-NO distances obtained from RNA (3,31) with those obtained from the Mn-NO results we assumed that addition of the equimolar amount of Mn 2+ did not alter the structure of the RNA significantly. 3d).…”
mentioning
confidence: 99%
“…3c. 40 In combining the NO-NO distances obtained from RNA (3,31) with those obtained from the Mn-NO results we assumed that addition of the equimolar amount of Mn 2+ did not alter the structure of the RNA significantly. 3d).…”
mentioning
confidence: 99%
“…59 It has recently been shown that Gd(III)-nitroxyl DEER measurements at the Q-and W band is yet another attractive approach for distance determination. 38,39,41 In this case, the effect of the pseudo-secular term should pose less of a problem, because the overlap between the nitroxyl radical transition and the Gd(III) transitions is limited to the broad background of the Gd(III) spectrum, and is attributed to transitions other than the central one. A theoretical analysis that takes into account the ZFS for such measurements has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Modifications of this approach involve the use of non-identical spin labels, in particular a Gd(III) center and a nitroxide [3,4], as well as different experimental schemes, such as relaxation-induced dipolar modulation (RIDME) [5] or continuous-wave EPR [6]. Distance measurements involving Gd spin labels have been successfully demonstrated on a number of systems, including model compounds, peptides, nanoparticles, proteins and DNAs [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Moreover, a promising biochemical property of Gd spin labels is the stability under reducing conditions, which recently enabled Gd-Gd distance measurements of peptides and proteins embedded in cellular environments [22,23].…”
Section: Introductionmentioning
confidence: 99%